Assessment of Pedestrian Mobility on Road Networks in the City of Kigali - Nkurunziza, David; Tafahomi, Rahman (Journal of Public Policy and Administration, 2023)
Purpose: The aim of this study is to analyze and assess the pedestrians' mobility issues that are affecting their free movement and safety in the City of Kigali by outlining the major challenges in the City and providing alternative solutions and measures for improving the mobility and safety of Pedestrians. Methodology: This study was designed based on qualitative method with application of structured and unobtrusive. Referring to the paper findings about the mobility challenges of pedestrians within the City of Kigali, it is noted that the mobility of the pedestrians and their safety is still low and typical problems including road crossing viewed as the second challenges about pedestrians mobility, walking along the road networks due to lack of footpaths, lacking of enough road signs, lacking of information about pedestrian behavior on road networks, and improper functioning of existing traffic signals as the first challenge. Findings: The study found that the majority of road networks in the City of Kigali did not provide walkways, traffics signals designs and availability is very poor and some of them not functioning, zebra crossing facilities were not provided adequately, pedestrians shelter on bus stop are almost absent and ignored, vehicles travelling speed is still high and does not allow pedestrians to move freely and the mobility of disables people has been forgotten and there is a need of introducing the pedestrian overpass bridges in clouded zones of Nyabugogo, Kicukiro Sonatube and Remera Giporoso areas of the City of Kigali. Unique Contribution to Theory, Practice and Policy: maintaining pedestrian's safety by using the traffic lights to warn the drivers to be aware of the pedestrians' safety and to think of how the implementation of the pedestrian overpass can be introduced in the City where more a great number of pedestrians crossing the road reduced to be killed in the accident.